COVID-19 Pandemic, Internal Audit Function and Audit Report Lag: Evidence from Emerging economy - Anas Rasheed Bajary; Rohami Shafie; Azharudin Ali (Cogent Business & Management, 2023)
With the spread of the COVID-19 pandemic, the accounting and auditing profession has been exposed to additional risks, challenges, and serious threats that affect audit quality; audit timeliness. Therefore, this study examines the effect of COVID-19 on audit reporting lag (ARL). In addition, this study investigates whether the internal corporate monitoring mechanisms contribute to mitigating the effect of the global health crisis; consequently, the study employs the internal audit function (IAF) cost as a moderator on the relationship between COVID-19 and ARL. To accomplish the objectives of our study, a sample of 1,352 firm-year observations from Malaysian listed firms was employed during the period 2017-2020, and feasible generalized least square (FGLS) regression was used. The findings indicate that auditors take longer to complete audit tasks and produce audit reports during COVID-19 than before. However, that period is obviously reduced with firms investing higher in their IAF. Furthermore, the findings obtained from the additional analyses and endogeneity tests support the main regression findings, thereby revealing that the findings are robust. The study's findings are among the earliest empirical evidence of the effect of COVID-19 on the ARL.
Keywords: 650; audit report lag; COVID-19; emerging economy; internal audit function; Malaysia